Navigating the family business: A gendered analysis of identity construction of daughters - Hytti Ulla; Alsos Gry Agnete; Heinonen Jarna; Ljunggren Elisabet (SAGE, 2022)
Previous research has explored the difficulties daughters experience entering family business management, but few studies have focused on their experiences of taking over a firm. A gender-as-a-variable perspective has been widely adopted, and the gendering of succession remains understudied. This article addresses this gap by conducting a gendered analysis of how daughters navigate family businesses and construct identities as family business leaders. Using narrative analysis and case study research, our findings suggest that daughters construct and negotiate their gender and leadership identities in their interactions with others by opposing, expanding and making use of the gendered scripts available to them. They move between concealing their leader identity and producing a masculinised identity as a strong owner. This necessitates tempered disruption and switching between different identities in different contexts. We conclude by discussing the theoretical aspects of a gendered perspective as they relate to identity construction in family businesses.